Cross-border Mergers and Acquisitions by Chinese Firms: an Analysis of Performances - XUE, Junlin (2016)
With the booming of the world economy, globalisation seems to have become an unavoidable trend, making each part of the world interrelated and interactive. During the past few decades, a large quantity of firms seeking growth and expansion have chosen merger and acquisition (M&A) as one of their main strategies. The United Nations Conference on Trade and Development (UNCTAD) states in 2000 that the amount of cross-border mergers has been on the rise and cross-border mergers have become the fasted means for those companies pursuing global expansion. Erel et al. (2012) stand for this point that the amount of international takeovers have dramatically increased from 23 percent in 1997 to 45 percent in 2002, and the majority of transactions are cross-border ones in developed country.